2011
DOI: 10.1007/s00228-011-1086-4
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin drug interactions: a comparative evaluation of the lists provided by five information sources

Abstract: Poor agreement was found among five sources listing warfarin interactions. Potentially severe clinical consequences might occur due to these discrepant recommendations. Finally, the lack of standard terminology and clinical guidance, as well as the possible inaccuracy of severity ratings and documentation might contribute to heterogeneous procedures in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 35 publications
1
29
0
8
Order By: Relevance
“…9 The difference in the total number of possible DDIs did not cause this discordance between most of the various DDI programs and it was suggested that this could be caused because of differences in the severity classification in these programs. [10][11][12][13] The concordance between the DDI programs used in the present study was high in terms of the number of patients detected with possible DDI in each program when compared with previous studies mentioned above. Although the DDI programs used in the present study were quite similar to each other according to the severity classification of possible DDIs, the concordances regarding the rate of severity ranking were low.…”
Section: Discussionsupporting
confidence: 52%
“…9 The difference in the total number of possible DDIs did not cause this discordance between most of the various DDI programs and it was suggested that this could be caused because of differences in the severity classification in these programs. [10][11][12][13] The concordance between the DDI programs used in the present study was high in terms of the number of patients detected with possible DDI in each program when compared with previous studies mentioned above. Although the DDI programs used in the present study were quite similar to each other according to the severity classification of possible DDIs, the concordances regarding the rate of severity ranking were low.…”
Section: Discussionsupporting
confidence: 52%
“…Racemic warfarin accumulates in the liver, in which both the R and the S enantiomers are metabolically transformed by different pathways [10]. The S enantiomer is approximately 90% oxidatively metabolized, primarily by the CYP2C9 enzyme of the CYP system and, to a lesser extent, by CYP3A4.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important causes of variability in warfarin response and fluctuating INR values is warfarin–drug interactions . Various drugs have been reported to interact with warfarin, which consequently represents a challenge to health care professionals to adjust and maintain the warfarin therapeutic response . The mechanism of interaction of these drugs with warfarin is either pharmacokinetic interaction by altering absorption, distribution, metabolism, and excretion of warfarin or by pharmacodynamic interaction by concomitantly prescribing drugs that cause additional impairment of coagulation .…”
mentioning
confidence: 99%
“…Other proposed mechanisms of interaction include alteration of absorption of warfarin by other drugs (eg, cholestyramine), disruption of vitamin K synthesizing gut flora (eg, broad‐spectrum antibiotics), displacement from plasma protein‐binding sites, and augmentation of anticoagulation by inhibiting platelet function (eg, aspirin and other antiplatelets) . There is a wide variability among information resources regarding warfarin–drug interactions . Warfarin–drug interactions reporting in the literature is often conflicting and generally poor in quality .…”
mentioning
confidence: 99%